Technology of Mechanical Processing of Materials (Texas Journal of Multidisciplinary Studies, 2022)
This article describes the technology of mechanical processing of materials. Flattening and milling of materials are similar processes, which means one- and two-sided processing of materials. Various tools and equipment are used in the mechanical processing of wood materials. They are used to cut, flatten, engrave and perform other technical processes. When processing wood materials, the flatness of the surfaces depends on what tools are used to make them.